Effects of pulmonary static inflation with 50% xenon on oxygen impairment during cardiopulmonary bypass for stanford type A acute aortic dissection: A pilot study - Jin, Mu; Yang, Yanwei; Pan, Xudong; Lu, Jiakai; Zhang, Zhiquan; Cheng, Weiping (Medicine (Baltimore), 2017)
The goal of this study was to investigate the effects of pulmonary static inflation with 50% xenon on postoperative oxygen impairment during cardiopulmonary bypass (CPB) for Stanford type A acute aortic dissection (AAD). This prospective single-center nonrandomized controlled clinical trial included 100 adult patients undergoing surgery for Stanford type A AAD at an academic hospital in China. Fifty subjects underwent pulmonary static inflation with 50% oxygen from January 2013 to January 2014, and 50 underwent inflation with 50% xenon from January 2014 to December 2014. During CPB, the lungs were inflated with either 50% xenon (xenon group) or 50% oxygen (control group) to maintain an airway pressure of 5 cm H2O. The primary outcome was oxygenation index (OI) value after intubation, and 10 minutes and 6 hours after the operation. The second outcome was cytokine and reactive oxygen species levels after intubation and 10 minutes, 6 hours, and 24 hours after the operation. Patients treated with xenon had lower OI levels compared to the control group before surgery (P = 0.002); however, there was no difference in postoperative values between the 2 groups. Following surgery, mean maximal OI values decreased by 18.8% and 33.8%, respectively, in the xenon and control groups. After surgery, the levels of interleukin-6 (IL-6), tumor necrosis factor alpha, and thromboxane B2 decreased by 23.5%, 9.1%, and 30.2%, respectively, in the xenon group, but increased by 10.8%, 26.2%, and 26.4%, respectively, in the control group. Moreover, IL-10 levels increased by 28% in the xenon group and decreased by 7.5% in the control group. There were significant time and treatment-time interaction effects on methane dicarboxylic aldehyde (P = 0.000 and P = 0.050, respectively) and myeloperoxidase (P = 0.000 and P = 0.001 in xenon and control groups, respectively). There was no difference in hospital mortality and 1-year survival rate between the 2 groups. Pulmonary static inflation with 50% xenon during CPB could attenuate OI decreases at the end of surgery for Stanford type A AAD. Thus, xenon may function by triggering anti-inflammatory responses and suppressing pro-inflammatory and oxidative effects.